Impaired Empathy Processing in Individuals with Internet Addiction Disorder: An Event-Related Potential Study - Jiao, Can; Wang, Ting; Peng, Xiaozhe; Cui, Fang (Frontiers in Human Neuroscience, 2017)
Internet addiction disorder (IAD) is associated with deficits in social communication and avoidance of social contacts. It has been hypothesized that people with IAD may have an impaired capacity for empathy. The purpose of the current study was to examine the processing of empathy for others’ pain in subjects with and without IAD. Event-related potentials (ERPs) produced in response to the pictures showing others in painful and non-painful situations were recorded in 16 IAD subjects and 16 healthy controls (HCs). The N1, N2, P3, and the late positive potential (LPP) components of recorded ERPs were compared between the two groups. Robust picture × group interactions were observed for N2 and P3. The painful pictures elicited larger N2 and P3 amplitudes than did non-painful pictures in the HC group but not in the IAD group. These results suggest that in both of the early automatic and the later cognitive process of other’s pain, the IADs show lower discrimination ability than the HCs. This study provides the psychophysical evidence of empathy deficits in association with IAD. Further studies combining multidimensional measurements of empathy are needed to confirm this finding.